Optimize the farming system to improve the physical and chemical properties of soil in Northeast China, thereby increasing maize yield - Qi, Xiangkun; Huang, Weidong; Li, Yicong; Xie, Jiachuang; Huang, Fenglin; Wang, Yufeng; Fu, Jian; Yang, Kejun (Frontiers in Plant Science, 2025)
Northeast China’s black soil region faces soil fertility decline, inadequate straw usage, and low maize yields. To address these issues, we conducted a two-year field experiment. The seven treatments comprised rotary ridge tillage (Con), no-tillage (T1), straw return + no-tillage (T2), deep-plowing straw return + ridge tillage (T3), deep-plowing straw return + flat tillage (T4), straw crushing and return + ridge tillage (T5), and straw crushing and return + flat tillage (T6). We examined the impact of various tillage methods on the structure of soil water-stable aggregates, soil nutrients, enzyme activity, and maize yield. The findings indicated that from 2021 to 2022, the soil macroaggregate content in the T4 considerably increased by 23.52% compared to the Con. Compared to Con, T4 significantly increased the mean weight diameter (MWD) and geometric mean diameter (GMD), enhancing soil fertility. Additionally, T4 reduced bald tip length while boosting the 100-Kernels weight by 24.01%, ultimately increasing maize yield by 13.62%. Consequently, deep-plowing straw return + flat tillage significantly enhanced soil structure, augmented soil fertility, and elevated maize production, rendering it the most appropriate tillage strategy for this region.